The Semidirect Sum of Lie Algebras and Its Applications to C-KdV Hierarchy. (27th May 2014) - Dong, Xia; Xia, Tiecheng; Li, Desheng
Abstract : By use of the loop algebra G - ~, integrable coupling of C-KdV hierarchy and its bi-Hamiltonian structures are obtained by Tu scheme and the quadratic-form identity. The method can be used to produce the integrable coupling and its Hamiltonian structures to the other integrable systems.